Pengelolaan Objek Wisata Sungai Gelombang Secara Berkelanjutan di Desa Sipungguk Kabupaten Kampar - Cavenes, Chania Arnata; Mashur, Dadang (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
The aim of this research is to find out and identify the existing conditions from 3 aspects, namely economic, social, environmental at the wave river tourist attraction and also to describe the sustainable management of the wave river tourist attraction.  The method used in this research uses descriptive qualitative methods and uses primary and secondary data, while data collection techniques use observation, interviews and documentation techniques.  The results of research on the sustainable management of the wave river tourist attraction in Sipungguk village kampar district, use four management functions seen from the planning of the sustainable management of the wave river tourist attraction in Sipungguk village kampar district.  surrounding communities, preserving the environment, empowering culture and traditional values.  The organization of sustainable management of the wave river tourist attraction in Sipungguk village kampar district, is fully managed by POKDARWIS from all development planning as well as economic, social and environmental aspects.  The implementation of sustainable management of the wave river tourist attraction in Sipungguk Village, Kampar Regency has not been fully implemented optimally in various plans from economic, social, environmental aspects and improvements to facility infrastructure.  Supervision of the management of the wave river tourist attraction in Sipungguk Village, kampar regency is continuously monitored regularly by POKDARWIS members in accordance with their respective functions and duties in the wave river tourist attraction area with the aim of being able to directly see the conditions of activities in the River Wave tourist attraction area.  Waves primarily ensures the comfort provided to visiting tourists.